Some characteristic features of the Japanese version of The Black Heralds - Matsumoto, Kenji (2020)
In the intricate process of translating The Complete Poetry of César Vallejo into Japanese, which was published in 2016 by the Gendai Kikakushitsu Publishing House in Tokyo, the most difficult challenge for the translator was, without doubt, the reproduction of the poetic language of The Blacks Heralds, because in this collection of poems, our poet is still looking for his own style, sometimes imitating the existing currents such as Spanish American modernismo. In contrast to the post-Trilce works of Vallejo, for which the translator could invent his own style «closed in itself», The Blacks Heralds, required him to access several corpus of the modern Japanese expression —the vocabulary of Japanese poets of the same period as The Blacks Heralds, and even the Japanese translated versions of Western poetry— to reproduce the complex poetic formation which beats in the book.